Understanding the impact of area-based interventions on area safety in deprived areas: realist evaluation of a neighbour nuisance intervention in Arnhem, the Netherlands - Daniëlle Kramer; Janneke Harting; Anton E. Kunst (BMC, 2016)
Abstract Background Area-based health inequalities may partly be explained by higher levels of area disorder in deprived areas. Area disorder may cause safety concerns and hence impair health. This study assessed how, for whom and in what conditions the intervention Meeting for Care and Nuisance (MCN) had an impact on neighbour nuisance and area safety in four deprived districts in Arnhem, the Netherlands. Methods Realist evaluation methodology was applied to uncover how, for whom, and under what conditions MCN was expected to and actually produced change. Expected change was based on action plans and scientific theories. Actual change was based on progress reports, media articles, interviews with district managers, and quantitative surveys. Results Three levels of impact were distinguished. At the organisational level, partly as expected, MCN's coordinated partnership strategy enabled role alignment, communication, and leadership. This resulted in a more efficient approach of nuisance households. At the level of nuisance households, as expected, MCN's joint assistance and enforcement strategy removed many of the underlying reasons for nuisance. This resulted in less neighbour nuisance. At the district level, perceptions of social control and area safety improved only in one district. Key conditions for change included a wider safety approach, dense population, and central location of the district within the city. Conclusions This realist evaluation provided insight into the mechanisms by which a complex area-based intervention was able to reduce neighbour nuisance in deprived areas. Depending on wider conditions, such a reduction in neighbour nuisance may or may not lead to improved perceptions of area safety at the district level.